2022
DOI: 10.1038/s41598-022-08731-x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in microanatomy of the human modiolus require individualized cochlear implantation

Abstract: Cochlear variability is of key importance for the clinical use of cochlear implants, the most successful neuroprosthetic device that is surgically placed into the cochlear scala tympani. Despite extensive literature on human cochlear variability, few information is available on the variability of the modiolar wall. In the present study, we analyzed 108 corrosion casts, 95 clinical cone beam computer tomographies (CTs) and 15 µCTs of human cochleae and observed modiolar variability of similar and larger extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Angular insertion depths of electrode carriers, expressed in degrees around the modiolus, vary due to interindividual anatomical differences, even if arrays of the same lengths are used ( 26 , 27 ). In humans, the height of the scala tympani starts to decrease at around 19 mm, reaching a critical point at approximately 23 mm, at an insertion angle of approximately 450 degrees measured from the round window ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angular insertion depths of electrode carriers, expressed in degrees around the modiolus, vary due to interindividual anatomical differences, even if arrays of the same lengths are used ( 26 , 27 ). In humans, the height of the scala tympani starts to decrease at around 19 mm, reaching a critical point at approximately 23 mm, at an insertion angle of approximately 450 degrees measured from the round window ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are characteristic ST properties (i.e. shape, length, cross sectional area) that can vary substantially between individuals [ 34 , 36 38 ]. This is highly relevant, as was shown by Dhanasingh et al [ 39 ], who showed that smaller sized ST phantoms yield higher insertion forces across different electrode array lengths.…”
Section: Introductionmentioning
confidence: 99%
“…An improved understanding of the position of the SCCs in space, based on a scannographic study, could make it possible to adapt vestibular functional explorations, in particular, head movements during VOR studies using the video head impulse test (VHIT). Numerous studies have focused on the anatomy of the cochlea [4,[7][8][9][10]. These studies have shown a great variability of the anatomy but with concordant results.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown a great variability of the anatomy but with concordant results. The methods of study were varied: either by indirect methods by multiple sections of the cochlea or by scannographic or µCT studies [4,[7][8][9][10]. The cochlear duct has a length of between 3.2-4.2 cm with high interindividual variability (relative standard deviation (RSD) > 1000% for the length of the basal turn and RSD > 800% for the total visible length of the cochlear duct) [4,7,8].…”
Section: Introductionmentioning
confidence: 99%